Assessing coaches` basic psychological need satisfaction and need frustration: preliminary validation from a multidimensional approach - Pulido, J. J.; López-Gajardo, M. A.; Díaz-García, J.; Tapia, M. A.; Leo, F. M. (International Journal of Sports Science & Coaching, 2022)
The purpose of this study was to adapt and validate the Basic Psychological Needs in Exercise (BPNES) and the Psychological Need Thwarting Scale (PNTS) to merge both measures and create a specific scale for the coaching context. Two studies were conducted. In Study 1, three sports psychologist experts adapted two instruments to analyze the coaches psychological needs on a single and multidimensional scale. Also, the content validity and comprehension of the scale were evaluated by 37 coaches (Mage = 33.03 ± 10.65; work experience = 8.79 ± 6.57 years). In Study 2, we tested other psychometric properties (i.e. confirmatory factor analysis, reliability, and concurrent validity) of the final version of the scale with 352 coaches (Mage = 32.88 ± 11.14; work experience = 8.03 ± 8.18 years) from four collective sports (soccer = 227; basketball = 69; handball = 43; and volleyball = 13). We tested a first-order six-factor solution of CBPN-Q and an H-CFA by including two second-order latent factors of need satisfaction and need frustration. The first-order six-factor solution obtained a better fit to the model than the H-CFA solution. The standardized factor loadings were positively significant and higher than.47. An adequate internal consistency was also obtained, and the concurrent validity of the scale was calculated with the types of motivation. These findings provide a valid and reliable scale to measure need satisfaction and need frustration in the field of coaching.